Canada's first bank : a history of the Bank of Montreal, vol 2 - Denison, Merrill (New York : Dodd, Mead, 1966)
The first volume of this history deals with the evolution of banking in Canada from its abortive beginning in the last decade of the eighteenth century to its permanent establishment in the fourth decade of the nineteenth century.
Vol. 2
Includes bibliographies.
osc 3/11/17
Loans
Keywords: Banking; Banking - canada; Canada